2012
DOI: 10.1111/j.1750-3841.2012.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Sugars, Organic Acids, and Total Phenolics in 25 Wild or Cultivated Berry Species

Abstract: The fruit of analyzed berry species contained different levels of sugars, organic acids, and total phenolics. Moreover, it has been demonstrated that wild grown species generally contain more phenolics than cultivated ones. This information is interesting for nutritionists as well as berry growers and breeders who can promote the cultivation of species and new cultivars with higher phenolic content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
263
7
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(336 citation statements)
references
References 33 publications
37
263
7
5
Order By: Relevance
“…Ozgen et al (2009) stated that the fructose and glucose contents of fourteen black and red mulberry genotypes ranged from 5.50 to 7.12 g 100 mL -1 and from 4.86 to 6.41 g 100 mL -1 , respectively. In another study, Mikulic-Petkovsek et al (2012) indicated that glucose and fructose determined in 25 wild and cultivated mulberries were more abundant, and the glucose content of black mulberry fruits growing wild in Slovenia was measured as 3.68 g 100 g -1 and the fructose content as 3.99 g 100 g -1 . The amounts of sugars determined in the fruits of mulberry cultivars and genotypes vary depending on genetic factors, cultivation practices, and environmental conditions (Gundogdu et al 2011).…”
Section: Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozgen et al (2009) stated that the fructose and glucose contents of fourteen black and red mulberry genotypes ranged from 5.50 to 7.12 g 100 mL -1 and from 4.86 to 6.41 g 100 mL -1 , respectively. In another study, Mikulic-Petkovsek et al (2012) indicated that glucose and fructose determined in 25 wild and cultivated mulberries were more abundant, and the glucose content of black mulberry fruits growing wild in Slovenia was measured as 3.68 g 100 g -1 and the fructose content as 3.99 g 100 g -1 . The amounts of sugars determined in the fruits of mulberry cultivars and genotypes vary depending on genetic factors, cultivation practices, and environmental conditions (Gundogdu et al 2011).…”
Section: Sugarsmentioning
confidence: 99%
“…Chemical content and antioxidant capacity of fruits are influenced by numerous factors. In particular, environmental conditions and genotype structure have great effects on the formation of these substances (Mikulic-Petkovsek et al 2012, Sanchez et al 2014. It has been revealed in several studies that the quality of local products made of particular wild or semi-wild edible fruits is also improved as a result of the high level of chemical components in mulberry species growing naturally in various regions of Turkey (Ercisli and Orhan 2008, Ozgen et al 2009, Gundogdu et al 2011, Orhan and Ercisli 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Diluted grape juice was centrifuged and filtrated. The separation of sugars and organic acids was done according to the HPLC method described by Mikulic-Petkovsek et al (2012a). The contents of all analyzed sugars and organic acids were expressed in g L -1 and summed up and presented as total sugar and acid contents in g L -1…”
Section: Extraction and Determination Of Sugars And Organic Acidsmentioning
confidence: 99%
“…The analysis of primary metabolites (sugars and organic acids) carried out using highperformance liquid chromatograph (HPLC) of Thermo Separation Products, as reported by (Mikulic-Petkovsek et al, 2012).…”
Section: Current Methods Used For Black Elder Chemical Characterizationmentioning
confidence: 99%